Ethical Governance in Public Service: A Comparative Study of Hadaya al-‘Ummal in Islamic Law and Gratification in Indonesian Law - H, Rajab; Paee, Rokiah; Thalhah; Nurdin, Rustina (NAJAHA, 2024)
Corruption continues to undermine governance, economic growth, and public trust in Indonesia. This study compares the Islamic concept of Hadaya al-’Ummal which strictly prohibits public officials from accepting any gifts that might compromise their integrity with the Indonesian legal framework on gratification, which permits gift acceptance provided that such benefits are reported within a specified period. Employing a qualitative comparative analysis grounded in Principal-Agent theory, the research examines five dimensions: the definition of gift-giving, the scope of recipients, legal sanctions, reporting mechanisms, and the handling of gifts. Data were collected from classical Islamic texts, legislative documents, and recent empirical studies to offer a comprehensive perspective on how ethical principles and legal measures interact in the context of corruption control. The findings reveal that Hadaya al-’Ummal offers a clear ethical guideline rooted in Islamic teachings, yet its informal enforcement limits its practicality in modern public institutions. In contrast, while the Indonesian legal framework provides explicit sanctions and formal reporting channels, its broad definitions and cultural nuances result in ambiguities and inconsistent application. High-profile cases have highlighted these challenges and underscored the need for clearer definitions and more effective oversight. The study argues that an integrated approach that refines legal definitions improves reporting systems and promotes comprehensive bureaucratic reforms while maintaining ethical accountability is essential to reduce corruption. These insights have important implications for developing anti-corruption strategies that enhance transparency, accountability, and ultimately, public trust.